2007
DOI: 10.1007/s10695-007-9174-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of photoperiod and melatonin in the regulation of ovarian functions in Indian carp Catla catla: basic information for future application

Abstract: The major carp Catla catla is a popular freshwater edible fish and an extensively cultured species in India. However, basic information on the physiology of reproduction is lacking in this species. By virtue of its surface feeding habit, it maintains close contact with environmental light, and is a species of choice for the study of temporal organization of reproduction under natural and experimental conditions for understanding environmental and/or endocrine mechanisms that control the annual reproductive cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Few studies have been conducted on the involvement of photoperiod with the reproductive activity of fish of tropical origin. Although the connection of temperature with reproductive activity cannot be ignored, the importance of photoperiod in reproductive activity was described in the cases of the Indian carp [14] and the sergeant major [13]. The experiments regarding the abovementioned factors were carried out in the sampling points around the subtropical regions of Santiniketan, India (23°14 0 N, 87°51 0 E) and São Paulo, Brazil (23°49 0 S, 45°22-25 0 W), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been conducted on the involvement of photoperiod with the reproductive activity of fish of tropical origin. Although the connection of temperature with reproductive activity cannot be ignored, the importance of photoperiod in reproductive activity was described in the cases of the Indian carp [14] and the sergeant major [13]. The experiments regarding the abovementioned factors were carried out in the sampling points around the subtropical regions of Santiniketan, India (23°14 0 N, 87°51 0 E) and São Paulo, Brazil (23°49 0 S, 45°22-25 0 W), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the influence of temperature is well documented in certain damselfish species [7,11,12]. It has also been reported that photoperiod is the most important environmental factor regulating the reproductive rhythm in the sergeant major Abudefduf saxatilis found in São Paulo, Brazil [13], and in the Indian carp Catla catla found in Santiniketan, India [14]. It is likely that the fish of tropical origin can respond flexibly to regional changes in various environmental cues in order to extend their breeding period and increase chances of reproductive success.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, the exploitation of several valuable cyprinid species for commercial purposes has made their investigation particularly relevant [11]. Catla is a species of choice for the study of temporal organization of reproduction under natural and experimental conditions for understanding environmental and/or endocrine mechanisms that control the annual reproductive cycle [12].…”
Section: Introductionmentioning
confidence: 99%
“…These results show how the photoperiod affects the reproduction of several fish species, interfering with the control of gonadal maturation and preparation for reproduction, so that out of their photoperiod genetically programmed by the species throughout its evolution, there is a delay or even inhibition of reproduction (Amano et al, 2000(Amano et al, , 2003Bromage et al, 2001;Maitra & Chattoraj, 2007).…”
Section: Resultsmentioning
confidence: 87%